1997
DOI: 10.1115/1.2798285
|View full text |Cite
|
Sign up to set email alerts
|

A Poroelastic Model That Predicts Some Phenomenological Responses of Ligaments and Tendons

Abstract: Experimental evidence suggests that the tensile behavior of tendons and ligaments is in part a function of tissue hydration. The models currently available do not offer a means by which the hydration effects might be explicitly explored. To study these effects, a finite element model of a collagen sub-fascicle, a substructure of tendon and ligament, was formulated. The model was microstructurally based, and simulated oriented collagen fibrils with elastic-orthotropic continuum elements. Poroelastic elements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 16 publications
1
49
0
Order By: Relevance
“…These include viscoelasticity of the collagen fibers (Rubin and Bodner, 2002), the extracellular matrix (Weiss et al, 2002), collagen fibril crosslinking (Bailey et al, 1974;Puxkandl et al, 2002;Redaelli et al, 2003) and fluid content (Chimich et al, 1992) and fluid movement within and in/out of the tissue during loading (Atkinson et al, 1997;Butler et al, 1997). However, most proposals have been based on conjecture and there is little experimental data available to support or refute the proposed mechanisms.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…These include viscoelasticity of the collagen fibers (Rubin and Bodner, 2002), the extracellular matrix (Weiss et al, 2002), collagen fibril crosslinking (Bailey et al, 1974;Puxkandl et al, 2002;Redaelli et al, 2003) and fluid content (Chimich et al, 1992) and fluid movement within and in/out of the tissue during loading (Atkinson et al, 1997;Butler et al, 1997). However, most proposals have been based on conjecture and there is little experimental data available to support or refute the proposed mechanisms.…”
Section: Introductionmentioning
confidence: 93%
“…The flow of water through a tissue in response to mechanical or chemical loading is governed by the apparent permeability, sometimes referred to as the hydraulic permeability (Holmes, 1985;Holmes and Mow, 1990;Mansour and Mow, 1976). In the case of ligaments, it has been suggested that the tissue may exhibit anisotropic permeability due to the highly aligned collagen fiber structure (Atkinson et al, 1997;Butler et al, 1997).…”
Section: O O Fmentioning
confidence: 99%
See 3 more Smart Citations